Impacto de uma intervenção teledirigida no perfil metabólico de pacientes com diabetes melito durante a pandemia de COVID-19 : um ensaio clínico randomizado - Franco, Débora Wilke (2022)
Background: The COVID-19 pandemic caused a failure in the provision of medical services that compromised the follow-up and possibly the adherence to the treatment of diabetes mellitus. Telemedicine entered this scenario attempting to reduce the damage caused to these individuals. Objectives: To evaluate the impact of a telehealth intervention on metabolic outcomes of patients with diabetes during the COVID-19 pandemic. Methods: This is a non-blind randomized controlled clinical trial to assess a telehealth intervention during the COVID-19 pandemic. We included adults with previous diabetes mellitus types 1 and 2 that regularly attended their specialist physicians in two tertiary health centers. The intervention included weekly phone calls (total of 16) and lasted 10 minutes each. The purpose of each phone call was to provide strategies for maintenance of healthy lifestyle. After the intervention, we evaluated and compared glycemic and metabolic profile between intervention and control group (people with diabetes from the same health center who did not receive our telehealth intervention). For statistical analysis Chi-square and T tests were performed. The initial analysis was a comparison with intention-to-treat of the primary outcome between intervention and control groups. Results: 150 individuals (58 patients with type 1 diabetes and 92 with type 2 diabetes) participated in the study; type 1 diabetes’s group had 94.8% white participants and 50% were female; type 2 diabetes’s group had 73.9% white participants and 65.2% were female. The mean age for type 1 diabetes group was 43.8 ± 13.5 and for type 2 diabetes group was 61.3 ± 9.0 years old. HbA1c values did not differ between intervention and control groups for neither type 1 (8.1% vs. 8.6 %; p=0.11) nor type 2 diabetes (8.6% vs. 9.0%; p=0.09), respectively. In secondary outcomes, a statistically significant change in triglyceride levels was observed for those individuals with type 1 diabetes (66.5% intervention group vs. 86.5% control group; p=0.05). Conclusions: Although previous studies have found the potential of enhancing treatment adherence with telehealth interventions, our findings were not able to identify significant improvements in glycemic control with a telehealth intervention. This highlights the need of other health care strategies to improve diabetes care during the social distancing period.